Il bello che cura. Benessere e spazi di accoglienza notturna per persone senza dimora - Campagnaro, Cristian; Porcellana, Valentina (Cambio. Rivista sulle Trasformazioni Sociali, 2016)
Looking into the housing services for homelessness leads to think about development of territory, citizens’ welfare, social recovery, reintegration into society and citizenship. Since 2009 the action-research, named “Living in the dorm”, has been investigating how architecture hosts services delivered to homeless people and how users interact with places and products in there. Spaces, pieces of furniture, tools, have been investigated and re-thought as part of the educational work carried out. Attention has been paid to the way spaces and objects interact with the biographies of the users and the operators and how these can qualify the service and act as enablers in the process of social inclusion.